SEARCHING FOR A NEW FOREIGN POLICY STRATEGY FOR AZERBAIJAN – PUBLIC DIPLOMACY EFFORTS - Aghazada, Rashad (European Scientific Journal, ESJ, 2014)
Nowadays public diplomacy is often investigated and analyzed in sociology in the context of the international public relations. This paper examines Public Diplomacy in general and Public Relations from a diplomatic perspective and its implications to the foreign policy of Azerbaijan. The article marks general features of the public diplomacy and the international public relations, also referring to sociological sources affirms the fundamental unity between public diplomacy and international public relations, investigates the difference of public diplomacy from traditional diplomacy. At the same time, the public diplomacy elements in Azerbaijan’s foreign policy and its chances in Nagorno Karabakh conflict solving are analyzed.